Immunochromatographic paper sensor for ultrasensitive colorimetric detection of cadmium - Shanshan Song (Taylor & Francis Group, 2018)
A novel and highly sensitive immunochromatographic strip based on a monoclonal antibody (3A9) was developed for the detection of cadmium in tap water. The 50% inhibition concentration of the antibody, which showed no cross-reactivity with other heavy metal ions, was 0.45 ng/mL and it recognized Cd(II)–1-(4-isothiocyanobenzyl) ethylenediamine-N,N,N′,N′-tetraacetic acid (EDTA) (Cd(II)–ITCBE) and not metal-free ITCBE and EDTA. The cutoff value for semi-quantitative detection of the strip was 5 ng/mL and the lower limit of detection for quantitative detection was 0.2 ng/mL using a scanning reader. The percent recovery ranged from 107.6% to 132% in tap water samples.